Вміст жиру, білку, соматичних клітин у молоці корів і кіз в залежності від кількості лактацій - Зажарська, Надія Миколаївна; Zazharska, Nadiia; Курбан, Дарина Анатоліївна; Kurban, Daryna; Голубева, Ольга Володимирівна; Нolubyeva, Olga (Дніпропетровський ДАЕУ, 2017)
Метою дослідження було визначення впливу номеру лактацій на показники молока корів і кіз, а, також, за породною ознакою у кіз. Досліджували проби молока від 17 кіз німецької білої, англо-нубійської і альпійської порід і 10 корів голштинської породи, на вміст жиру, білку, соматичних клітин за період чотирьох лактацій. Показники жиру і білку молока залежать головним чином від якості годівлі, а не від номеру лактації. Вміст соматичних клітин в коров’ячому молоці 2-ої, 3-ої, 4-ої лактацій більше у 5,2, 4,6 і 4,9 раза відповідно від показника першої лактації (Р < 0,05). В молоці кіз і корів першої лактації відмічається найменша кількість соматичних клітин за все життя тварини. Потім в молоці корів кількість соматичних клітин збільшується і реєструються на рівні 169–192 тис/мл. В молоці кіз кількість соматичних клітин з другої по четверту лактації зафіксовано на рівні 793–930 тис/мл. В цілому, не відмічено збільшення кількості соматичних клітин з віком корови або кози, тобто з номером лактації. Відсутня породна схильність до зменшення або збільшення кількості соматичних клітин, вмісту жиру і білку у молоці кіз за період чотирьох лактацій. У кіз альпійської породи кількість соматичних клітин збільшується у три рази за період від першої до другої лактації, у той час, як у кіз англо-нубійської і німецької білої породи цей показник знижується на 5,1 і 31,7% відповідно за той самий період, що доводить велику мінливість даного показника. The purpose of the study was to determine the effect of the number of lactation on the indicators of milk of cows and goats, and, also, on a breed characteristic in goats. The samples of milk from 17 goats of German white, Anglo-Nubian and Alpine breeds and 10 cows of Holstein breed, on the content of fat, protein, somatic cells during the period of four lactations were analyzed. The biochemical indexes of milk were determined by means of ultrasonic analyzer of milk of «Ekomilk type MILKANA KAM 98-2a» and «Dairy Spec Bentley Instruments». The somatic cells in individual milk samples were analyzed by viscometric analyzer «Somatos-M» and flow cytometr «SomaCount Bentley Instruments». The indicators of milk fat and protein depend on the quality of feeding mainly, and not on the number of lactation. During the period from the first to the second lactation the increasing of the cows’ productivity was observed: an increase in the daily yield of 5 kg and 6 kg in the period from the first to the second and to the third lactation (Р < 0,05; Р<0,01 respectively). The somatic cell count in cow's milk of the 2nd, 3rd, 4th lactation was more at 5,2, 4,6 and 4,9 times respectively, according to the content during the first lactation (Р < 0,05). The smallest somatic cells count was observed in the milk of goats and cows of the first lactation, in comparing, throughout the life of the researched animals. Then in the milk of cows the somatic cell count was increasing and it was recorded at the level of 169-192 ×10³ cells/ml. In the milk of goats, the somatic cell count from the second to fourth lactations was recorded at the level of 793-930 ×10³ cells/ml. In general, there was no increasing of the somatic cell count according to the age of cows or goats, that means, with the number of lactation. Breed and genetic predisposition to reducing or increasing of the somatic cell count wasn’t noticed, as well as, the quantity of fat and protein in the milk of goats during the period of four lactations. In Alpine breed goats, the somatic cell count increased in three times during the period from the first to the second lactation, while in the Anglo-Nubian and German white breeds it had decreased by 5.1 and 31.7% respectively for the same period , which proves the great variability of this indicator.
Contain of fat, protein, somatic cells in cow's and goat's milk depending on number of lactation
Keywords: козине молоко; goat's milk; коров’яче молоко; cow's milk; кількість соматичних клітин; somatic cell count; фізико-хімічні показники; physical and chemical indexes; лактація; lactation